Znaczenie strategicznej karty wyników w controllingu procesów - Czyż-Gwiazda, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
At the present the meaning of BSC is still increasing. There are many reasons of this situation. One of the most important think is change in the business orientation. Enterprises focus their energy around clients and their needs. The human, client is in the middle of all company's activities. It causes, that now the right suitable business orientation is the business process orientation. Through the business process orientation and using the right tools companies can achieve the competitive advantage. Important and useful tool for managers, which they can use in process controlling, it seems to be the BSC. The managers can use it in their enterprises directly and fit it to the organization's needs or they can use another framework being better suitable to the company's strategy. After choosing the framework, the company should select the suitable measures to each process. Only the permanently process controlling based on the defined measures from for example BSC can supply to managers and the process's owners the whole of needed data to take the right decision in the right time. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 57-67